Integrasi Literasi Digital dan Teknologi sebagai Transformasi Metode Pendidikan Nabi Muhammad dalam Konteks Pembelajaran Abad ke-21 - Hanif, Tegar; Fatimah, Fatimah; Wahyuni, Sri; Misbah, M. (Lembaga Yasin AlSys, 2025)
Education grounded in the teachings of Prophet Muhammad SAW should be capable of addressing humanistic dimensions in a manner relevant to the 21st-century context. This study aims to explore the integration of digital literacy and technology into the transformation of educational methods practiced by Prophet Muhammad SAW, focusing on their relevance to contemporary learning needs. A qualitative-descriptive literature review approach was employed to analyze the Prophet’s educational principles, including effective communication, dialogue-based learning, and character formation. The findings indicate that the Prophet’s contextual, participatory, and interactive teaching methods are highly adaptable to modern digital learning environments. The study also reveals that the use of digital technologies—including online learning platforms and social media—can enhance learners’ collaboration, creativity, and problem-solving skills. Despite challenges in implementation, this integration presents opportunities to foster holistic, relevant, and meaningful learning experiences. These findings affirm that applying the educational principles of Prophet Muhammad SAW through digital literacy holds strategic potential for developing an adaptive and transformative education system in the technological era.